EUROSOI-ULIS 2015: 2015 Joint International EUROSOI Workshop and International Conference on Ultimate Integration on Silicon 2015
DOI: 10.1109/ulis.2015.7063793
|View full text |Cite
|
Sign up to set email alerts
|

Efficient quantum mechanical simulation of band-to-band tunneling

Abstract: In this work, we extend an already existing simulator for tunnel FETs to fully take into account nonparabolicity (NP) of the conduction band in all aspects, namely the wavefunction (WF) and density of states (DOS) corrections for both charge and BTBT current calculation. Comparison against more advanced full-quantum simulators based on TB and k · p Hamiltonians is presented as well and indicates very good matching between models for simple tunnel diodes. An initial parameter study of the Electron Hole Bilayer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This is due to the use of a direct tunneling matrix element in Agarwal et al that largely differs from the phonon assisted tunneling one [16] that we found to be dominant in Si and Ge devices. Even though direct BTBT is dominant in Ge for bulk 3D-3D tunneling [8], quantization essentially suppresses the direct BTBT in the ON state of the Ge EHBTFET for all the cases considered in this study. Regarding InAs, instead, our results are only 5-10 times lower than the ones in [6] mainly due to the inclusion in our model of the effect of quantization on the matrix element (term C 0 (θ) in Eq.…”
Section: Performance Considerations and Impact Of Channel Materialsmentioning
confidence: 86%
See 4 more Smart Citations
“…This is due to the use of a direct tunneling matrix element in Agarwal et al that largely differs from the phonon assisted tunneling one [16] that we found to be dominant in Si and Ge devices. Even though direct BTBT is dominant in Ge for bulk 3D-3D tunneling [8], quantization essentially suppresses the direct BTBT in the ON state of the Ge EHBTFET for all the cases considered in this study. Regarding InAs, instead, our results are only 5-10 times lower than the ones in [6] mainly due to the inclusion in our model of the effect of quantization on the matrix element (term C 0 (θ) in Eq.…”
Section: Performance Considerations and Impact Of Channel Materialsmentioning
confidence: 86%
“…The simulator solves the Schrödinger and Poisson equations self-consistently under the effective mass approximation with non-parabolicity corrections [8]. Self-consistency is achieved using the non-linear Schrodinger-Poisson scheme [9].…”
Section: Numerical Model Description and General Frameworkmentioning
confidence: 99%
See 3 more Smart Citations